AUDIENCE ADAPTATION DALAM GAYA BERPAKAIAN (Studi Deskriptif Kualitatif Trend Jilboobs Pada Mahasiswi Yogyakarta) - Fendi Rahmat Widianto (Profetik: Jurnal Komunikasi, 2015)
This research aim to describe the Audience Adaptation process using descriptive qualitative method with primary and secondary data sources. Based on that some people may good at entertaining others, but some others good at comforting people. Its influenced by cognitive complexity from each person. Cognitive complexity control how people producing message in communication process. One of the process is how people select fashion for themselves. Fashion selection influenced by messages which are obtained by people from outside and intepreted by themselves then send it to others in fashion form represent of themselves, this process called Audience Adaptation.Datas from this research are transcript of depth-interview, support documents, and support pictures. This research using Analysis Data Method from Cresswell. This research see how youth muslimah in Yogyakarta when it comes to Audience Adaptation of fashion hijab especially Jilboobs phenomenon. Youth muslimah tend to following hijab trend and unobservant of religion’s rules, so they tend to use fashion hijab as they want to be. Freedom of fashion caused Jilboobs phenomenon and its brought shame on interpersonal construct of muslimah Indonesia especially as people who obey their religion. Youth muslimah Yogyakarta sent their person centered messages in form of Jilboobs to seeks personal satisfaction and try to get public attention indirectly.